Growth Mechanism of a Hybrid Structure Consisting of a Graphite Layer on Top of Vertical Carbon Nanotubes. (9th September 2012) - Chiodarelli, Nicolo'; Xu, Cigang; Richard, Olivier; Bender, Hugo; Klekachev, Alexander; Cooke, Mike; Heyns, Marc; De Gendt, Stefan; Groeseneken, Guido; Vereecken, Philippe M.
Abstract : Graphene and carbon nanotubes (CNTs) are both carbon-based materials with remarkable optical and electronic properties which, among others, may find applications as transparent electrodes or as interconnects in microchips, respectively. This work reports on the formation of a hybrid structure composed of a graphitic carbon layer on top of vertical CNT in a single deposition process. The mechanism of deposition is explained according to the thickness of catalyst used and the atypical growth conditions. Key factors dictating the hybrid growth are the film thickness and the time dynamic through which the catalyst film dewets and transforms into nanoparticles. The results support the similarities between chemical vapor deposition processes for graphene, graphite, and CNT.